IEEE Symposium on Information Visualization
DOI: 10.1109/infvis.2004.60
|View full text |Cite
|
Sign up to set email alerts
|

Steerable, Progressive Multidimensional Scaling

Abstract: Current implementations of Multidimensional Scaling (MDS), an approach that attempts to best represent data point similarity in a low-dimensional representation, are not suited for many of today's large-scale datasets. We propose an extension to the spring model approach that allows the user to interactively explore datasets that are far beyond the scale of previous implementations of MDS.We present MDSteer, a steerable MDS computation engine and visualization tool that progressively computes an MDS layout and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
1

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 17 publications
0
64
0
1
Order By: Relevance
“…Other cognitive traits too have also been shown to have a strong influence on users' performance. The study by Conati and Maclaren [7] looked at two different visualizations to represent changes in a set of variables: a radar graph and a Multiscale Dimension Visualizer (MDV); a visualization that primarily uses color hue and intensity to represent change direction and magnitude [23]. They found that: (1) a user's perceptual speed was a significant predictor of which of the two visualizations would work better for that user on a specific comparison task, and (2) both perceptual speed and visual spatial working memory were predictors of performance with each visualization for some of the study's tasks.…”
Section: Related Workmentioning
confidence: 99%
“…Other cognitive traits too have also been shown to have a strong influence on users' performance. The study by Conati and Maclaren [7] looked at two different visualizations to represent changes in a set of variables: a radar graph and a Multiscale Dimension Visualizer (MDV); a visualization that primarily uses color hue and intensity to represent change direction and magnitude [23]. They found that: (1) a user's perceptual speed was a significant predictor of which of the two visualizations would work better for that user on a specific comparison task, and (2) both perceptual speed and visual spatial working memory were predictors of performance with each visualization for some of the study's tasks.…”
Section: Related Workmentioning
confidence: 99%
“…As algorithms get more and more complex and tend to carry black-box characteristics, interpreting an algorithmic outcome is increasingly gaining importance. Recent examples by the Google Big Picture team 4 or promising innovative publications such as Distill.pub 5 are demonstrating how an effective use of visualization can help unravel algorithms and make them more accessible for wider audiences and also help in educational purposes. However, examples so far are often designed case-by-case basis and further research is needed to develop guidelines, best-practices and a systematic characterization of the role and scope of visualization and interaction.…”
Section: Challenges and Opportunities For Researchmentioning
confidence: 99%
“…The field of visualization, and in particular visual analytics, is a discipline that is motivated by these complex problems that require a concerted effort from computational methods and the human analyst to be addressed [3]. Expert users have the domain knowledge to steer algorithmic power to where it is needed the most [4], and offer the capability and creativity to fine-tune computational results and turn them into data-informed decisions [5]. As a growing field, there are already several effective examples where the combination of visualisation and machine learning are being developed to offer novel solutions for data-intensive problems [1].…”
Section: Introductionmentioning
confidence: 99%
“…[51], [52], [53], [54], [55], [56] Groups & Classification [57] [58], [59] [60], [61], [62], [63], [64], [65], [66], [67], [68], [69], [70], [71], [72], [73], [74] [75], [76], [77], [78], [79], [80] Dependence & Prediction [81], [82], [46] [83], [84], [85], [86], [87], [88], [89] [90], [91], [92] being analyzed. The results are then presented to the user through different visual encodings that are often accompanied by interaction.…”
Section: Levels Of Integrationmentioning
confidence: 99%
“…In MDSteer [52], an embedding is guided with user interaction leading to an adapted multidimensional scaling of multivariate data sets. Such a mechanism enables the analyst to steer the computational resources accordingly to areas where more precision is needed.…”
Section: Tight Integrationmentioning
confidence: 99%